KEBIJAKAN PEMERINTAH KOTA PALANGKA RAYA TERHADAP PERLINDUNGAN HUKUM PEREMPUAN DAN ANAK DI TENGAH PANDEMI COVID-19: Policy Of The City Of Palangka Raya Government On The Legal Protection Of Women And Childern In The Middle Of The COVID-19 Pandemic - Rahmaniati, Rita; Sanawiah, Sanawiah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This study aims to describe the policy of the Palangka Raya city government towards the legal protection of women and children in the midst of the covid-19 pandemic. The type of research used is a qualitative research method. Sources of data in this study consisted of primary data and secondary data. The primary data are PPKBPPPAPM Office of Palangka Raya City, Head of Women and Children Empowerment Office of PPKBPPPAPM Office of Palangka Raya City and Manager of Posbakum Aisyiah City of Palangka Raya, while secondary data sources are instructions and policies of the City Government. Based on the results of the study, it can be explained that the Palangkaraya city government's policy towards legal protection of women and children in the midst of the covid-19 pandemic is very good. The city government through the PPKBPPPAPM Office of Palangka Raya City, in providing protection and empowerment of women, conducts counseling on family resilience as well as holding skills training for mothers in order to improve the community's economy in the midst of the Covid-19 pandemic, so that women in the household become independent, not dependent on their husbands, increase family welfare and better maintain health, so that physical and non-physical violence can be avoided.